Infusion phlebitis assessment method used in paediatric setting: a systematic review of literature - Chong, Li Tsu; Deena Clare Thomas; Renie Martha Joanes; Rose A Nain (Malaysian Journal of Medicine and Health Sciences, 2020)
Phlebitis may localise to the insertion site or travel along the vein. The risk of phlebitis is higher in children as they have thin and weak blood vessels and move continuously due to the pain associated with insertion. Therefore, regular assessment of the risk of developing phlebitis is crucial. This review aimed to identify infusion phlebitis assessment tool used in the paediatric setting. Methods: Electronic databases used were Scopus, ProQuest, ScienceDirect, and Google Scholar. A total of ten studies which assess the development of infusion phlebitis on hospitalised children included in this reviewed. Study findings were discussed and concluded with a recommendation for clinical practice and future studies. Results: Phlebitis development rate was the primary outcome measures in ten studies. Of ten studies, six provided no actual definition of phlebitis. Eight reported phlebitis incidence and/or severity, eight used a scale and two used a definition alone in assessing the development of phlebitis. This review identified five different phlebitis assessment scales. Conclusion: Although there are applicable phlebitis scales can be used for paediatric setting, Limited studies have been conducted on infusion phlebitis assessment method in children. Therefore, it is suggested that more studies and vigorous test needed to identify applicable assessment tools in paediatric setting.